PENGARUH KOMPETENSI, ETIKA, DAN PENGALAMAN KERJA TERHADAP KUALITAS AUDITOR INTERNAL - Muhammad Laras Widyanto; Febrian Kwarto; Sri Kurniawati (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2018)
The banking system will run well if all parts work well and synergize according to the function, the Internal Auditor has clear and legal authority to carry out the internal control and control functions. The quality of internal audit will be one of the benchmarks of whether a banking system can work well or not. The quality of good internal audit is the implementation of competence, ethics, and maximum work experience The purpose of this study is to determine how much influence ethics competence,, and work experience on audit quality both simultaneously and partially Data collection techniques in the study were questionnaires tested through descriptive analysis and multiple linear regression. The population in this study are the Internal Auditors at conventional bank in Tangerang city. The results showed that Competence positively influence the Quality of Auditors, while Ethics and Work Experience partially does not affect the Quality of Auditors Keywords: Competence, Ethics, Auditor Experience, Quality of Auditors